Pharmacognostic, chemical and mucolytic activity study of Malva pseudolavatera Webb & Berthel. and Malva sylvestris L. (Malvaceae) leaf extracts, grown in Ecuador - Migdalia Miranda-Martínez; GLENDA MARCELA SARMIENTO-TOMALÁ; IVÁN ANDRÉS CHÓEZ-GUARANDA; YAMILET IRENE GUTIÉRREZ-GAITÉN; RENÉ DELGADO-HERNÁNDEZ; GABRIELA CARRILLO-LAVID (Society for Indonesian Biodiversity, 2020)
Abstract.  Sarmiento-Tomalá GM, Miranda-Martínez M, Chóez-Guaranda IA, Gutiérrez-Gaitén YI, Delgado-Hernández R, Carrillo-Lavid G. 2020. Pharmacognostic, chemical and mucolytic activity study of Malva pseudolavatera Webb & Berthel. and Malva sylvestris L. (Malvaceae) leaf extracts, grown in Ecuador. Biodiversitas 21: 4755-4763.  Among the cultivated and/or native plant species of Ecuador, are those belonging to Malvaceae. Of these, the most traditionally used are Malva pseudolavatera Webb & Berthel. and Malva sylvestris L., which are grown and sold in indigenous markets. Various articles have been published for M. sylvestris about its chemical composition and pharmacological properties; however, M. pseudolavatera lacks references and is the most commercialized in Ecuador. Therefore, this work sets the following objective: To carry out a comparative study of the pharmacognostic, chemical and mucolytic activity of the species M. pseudolavatera and M. sylvestris. The species studied were collected in the province of Chimborazo. Extracts were obtained with different solvents: water, hexane and 80% ethanol. The aqueous extract was used to determine the mucolytic activity; the hexane and alcoholic extracts were analyzed by the coupled gas chromatography-mass spectrometry system. It was found that M. pseudolavatera has a very similar chemical composition to M. sylvestris; The presence of fatty acids, di and triterpenoids, phytosterols and abundant amino acids was detected. Both species showed an important mucolytic effect, the activity of M. pseudolavatera being higher than the highest doses tested. These studies provide scientific data that allow demonstrating the high potentiality of extracts from the leaves of two Malva species as sources of plant material for possible research and development of phytotherapeutic products with mucolytic and gastroprotective activity in correspondence with their uses in traditional Ecuadorian herbal medicine.